PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN DARING MENGGUNAKAN GOOGLE SITES PADA GURU SMIT BINA AMAL SEMARANG - Rachmawati, Eka Putri; Widodo, Edi; Christioko, Bernadus Very (Jurnal DIMASTIK, 2023)
PKM in the form of training conducted by lecturers from Semarang University and SMIT Bina Amal Semarang, aims to teach teachers in the SMIT Bina Amal environment about the use of Google Sites as a means of supporting the teaching and learning process. The training covers the features and benefits of Google Sites, including its ease of use, flexibility, and integration with other Google tools. It provides practical tips and best practices for using Google Sites in an educational context, including creating and organizing content, facilitating student engagement and collaboration, and assessing student learning. Overall, the training highlights the potential of Google Sites to support effective and engaging online learning experiences for both students and teachers. The results of the project were overwhelmingly positive, with teachers reporting improved ease of use and efficiency in delivering materials. The use of Google Sites also allowed for more effective communication between teachers and students, and the platform proved particularly useful for delivering materials in a setting with limited resources and infrastructure. Their experience can serve as a model for other schools looking to implement similar initiatives, and the benefits of using technology for education can be further explored and harnessed in the years to come.